Spatiotemporal distribution of flavescence dorée phytoplasma in grapevine. (10th October 2012) - Prezelj, N.; Nikolić, P.; Gruden, K.; Ravnikar, M.; Dermastia, M.
<x xml:space="preserve">Abstract</x> In this study quantitative real‐time PCR was used to follow the seasonal changes of flavescence dorée phytoplasma (FDp) titre in grapevines of cv. Modra frankinja (syn. Blaufränkisch) and cv. Refošk (syn. Refosco'd'Istria) from two vineyards located in climatically different vine‐growing regions of Slovenia. Besides its known presence in the leaf veins, FDp was also detected in flowers, berry tissues and tendrils. In plants with high concentrations of FDp in tissues with symptoms, phytoplasma was also detected in symptomless tissues. A trend of decreasing FDp titre in all examined symptomless tissues from June to July and an increasing one throughout the growing season in tissues with symptoms was recorded. Accordingly, FDp was present in detectable amounts in flowers, petioles and veins of almost all infected plants in the late spring, and was detected in all examined tissue types in summer, with the highest titre in berries in August. The study showed that in the absence of plant health measurements an FDp infection may spread exponentially by a factor of 40 per year.